Inactivation of escherichia coli under fluorescent lamp using TiO2 nanoparticles syntesized via sol gel method (Penyahaktifan Escherichia coli di bawah Lampu Pendarfluor menggunakan Nanozarah TiO2 yang Disintesis melalui kaedah Sol Gel) - Sapizah Rahim; Shahidan Radiman; Ainon Hamzah (Universiti Kebangsaan Malaysia, 2012)
Titanium dioxide nanoparticles were synthesized by using sol gel method and their physico-chemical properties were characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and UV-Vis spectrophotometer. The photocatalytic property of TiO2 nanoparticles was investigated by inactivation of Escherichia coli under irradiation of fluorescent lamp. The results showed that the size of TiO2 was in the range of 3 to 7 nm with high crystallinity of anatase phase. The sharp peaks in FTIR spectrum determined the purity of TiO2 nanoparticles and absorbance peak of UV-Vis spectrum showed the energy band gap of 3.2 eV. Optimum inactivation of E. coli was obtained at 1.0 g/L TiO2 nanoparticles, with 80% of E. coli population was inactivated. The light scattering effect and insufficient concentration are the factors that cause the less effective inactivation reaction for 2.5 g/L and 0.1 g/L TiO2 concentration